Pengaruh customer review, customer rating, dan celebrity endorser terhadap minat beli melalui kepercayaan di online shop Shopee - Firdaus, Mukhammad; Aisyah, Siti; Farida, Eka (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2023)
Shopee is the number 1 marketplace in Indonesia in terms of usage, but lately Shopee is no longer in that position. The aim of this research is to find out and analyze how the influence of Customer Reviews, Customer Ratings and Celebrity Endorsers on Purchase Intention through trust as an intervening variable at Online Shop Shopee. This research is a quantitative research using explanatory research techniques. The sampling was carried out using purposive sampling technique. The population of this research is all Shopee consumers in Malang city with 95 respondents as a sample. The results of this study are (1) Customer reviews have no significant effect on trust, (2) Customer ratings and celebrity endorsers have a significant effect on trust, (3) Customer reviews have no significant effect on purchase intention, (4) Customer ratings and celebrity endorsers have a significant effect on purchase intention, (5) Trust has an effect on purchase intention, (6) Customer reviews have no significant effect on purchase intention through trust, (7) Customer ratings and celebrity endorsers have a significant effect on purchase intention through trust.